Acute toxicity of some nerve agents and pesticides in rats - Misik, Jan; Pavlikova, Ruzena; Cabal, Jiri; Kuca, Kamil (Drug and chemical toxicology, 2015)
OBJECTIVES: Highly toxic organophosphorus compounds (V- and G-nerve agents) were originally synthesized for warfare or as agricultural pesticides. Data on their acute toxicity are rare and patchy. Therefore, there is a need for integrated summary comparing acute toxicity of organophosphates using different administration routes in the same animal model with the same methodology. Based on original data, a summary of in vivo acute toxicity of selected V- and G-nerve agents (tabun, sarin, soman, VX, Russian VX) and organophosphates paraoxon (POX) and diisopropyl fluorophosphate (DFP) in rats has been investigated. MATERIALS AND METHODS: Male Wistar rats were exposed to organophosphates in several administration routes (i.m., i.p., p.o, s.c., p.c.). The acute toxicity was evaluated by the assessment of median lethal dose (LD50, mg kg(-1)) 2, 4, and 24 hours post exposure. RESULTS: V-agents were the most toxic presented with LD50 ranged from 0.0082 mg kg(-1) (VX, i.m.) to 1.402 mg kg(-1) (Russian VX, p.o.), followed by G-agents (LD50 = 0.069 mg kg(-1)/soman, i.m./ - 117.9 mg kg(-1)/sarin, p.c./), organophosphate POX and DFP (LD50 = 0.321 mg kg(-1)/POX, i.m./ - 420 mg kg(-1)/DFP, p.c./). Generally, i.m. administration was the most toxic throughout all tested agents and ways of administration (LD50 = 0.0082 mg kg(-1)/VX/ - 1.399 mg kg(-1)/DFP/) whereas p.c. way was responsible for lowest acute toxicity (LD50 = 0.085 mg kg(-1)/VX/ - 420 mg kg(-1)/DFP/). CONCLUSION: The acute toxicity of selected organophosphorus compounds is summarized throughout this study. Although the data assessed in rats are rather illustrative prediction for human, it presents a valuable contribution, indicating the toxic potential and harmfulness of organophosphates.
Keywords: Pesticides; Chemical warfare agent; Administration, Oral; Male; Chemical Warfare Agents; pesticidy; Rats, Wistar; Injections, Subcutaneous; chemické bojové látky; injekce intramuskulární; organofosforové sloučeniny; aplikace kožní; LD50; molekulární struktura; G-agents; Molecular Structure; aplikace orální; V-agents; mužské pohlaví; potkani Wistar; Toxicity Tests, Acute; organophosphate; Animals; Organophosphorus Compounds; zvířata; Lethal Dose 50; military toxicology; testy akutní toxicity; Injections, Intramuscular; injekce subkutánní; Administration, Cutaneous